2010
DOI: 10.1136/qshc.2008.031690
|View full text |Cite
|
Sign up to set email alerts
|

The importance of experienced adverse outcomes on patients' future choice of a hospital for surgery

Abstract: Adverse outcome experience may change the information patients use (on quality of care) to choose a future hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 14 publications
2
25
0
2
Order By: Relevance
“…However, most studies investigating real choices found that outcome indicators have a limited influence on patients’ choices. This difference is confirmed by research that directly compared revealed preferences against stated preferences [30,45,46,48,49]. Exceptions are results from studies analysing patient registration data.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…However, most studies investigating real choices found that outcome indicators have a limited influence on patients’ choices. This difference is confirmed by research that directly compared revealed preferences against stated preferences [30,45,46,48,49]. Exceptions are results from studies analysing patient registration data.…”
Section: Discussionmentioning
confidence: 89%
“…Often, patients who do find this information relevant eventually do not use it, which suggests that there is a difference between what patients say and what they actually do [16,31,64]. This difference is confirmed by research that directly compared revealed preferences against stated preferences [30,45,46,48,49]. Patients use more comparative information in future choices and in advice to others than they used in previous choices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 It can be hypothesized that the attribute percentage of patients with "textbook outcomes" has greater impact on patients' choices if they have experienced adverse outcomes, as the occurrence of adverse outcomes is part of this attribute. We therefore assessed whether the relative importance patients assigned to this attribute differed between patients with and without adverse outcomes during their initial hospitalization or after discharge, using oneway analysis of variance with post hoc Bonferroni or Tamhane tests for multiple comparisons.…”
Section: Analysesmentioning
confidence: 99%
“…In contrast to most previous studies, this study focuses on possibilities to empower patients to take active choices, in particular by bringing in the concept of targeted transparency taken from Fung, Graham & Weil's book "Full Disclosure" (2007). Many scholars have invested a lot of time and effort into assessing whether and how patients in the Netherlands are using PQR tools with interviews Damman et al, 2009;de Groot et al, 2010;Marang-van de Mheen et al, 2010;Moser et al, 2010;Ketelaar et al, 2014;Victoor et al, 2014). However, all of these contributions only provided, if at all, a discussion of their findings in the light of studies from the USA or the UK.…”
Section: Gaps In Existing Researchmentioning
confidence: 99%